MECHANISMS OF EDUCATIONAL STUDY OF STUDENTS ON THE BASIS OF MODERN PEDAGOGICAL TECHNOLOGIES - Tangirov Eldor Sayfullayevich (Journals Park Publishing, 2022)
The article analyzes the modern educational technologies applied in the learning process, composite activity and to the creative development of the student: technology contextual learning, project-based learning technology, interactive technology (discussions, debates, moderation), technology education workshops, technology training of students with signs of giftedness. Justified the use of these technologies in vocational training of bachelors in the development of student-centered education.
Keywords: personality-oriented; education; modern educational technology